Comparison of perfluoroalkyl substances contamination in farmed and wild-caught European sea bass (Dicentrarchus labrax) - Barbarossa, Andrea; Gazzotti, Teresa; Farabegoli, Federica; Mancini, Francesca Romana; Zironi, Elisa; Badiani, Anna; Busani, Luca; Pagliuca, Giampiero (Food control, 2016)
Perfluoroalkyl substances (PFASs) are a family of persistent pollutants of anthropic origin which can reach humans mainly through diet, causing potentially dangerous effects on health. Fish and fishery products are a major source of exposure, but intra- and inter-specific contamination can be extremely variable. In the present study a single species monitoring of the presence of perfluorooctane sulfonate (PFOS) and perfluorooctanoic acid (PFOA), the two main compounds of the family, was performed on 140 farmed and wild caught European sea basses (Dicentrarchus labrax) from different places in the Mediterranean area. The results highlight a strong correlation between the level of contamination and the origin of fishes, if wild or farmed: on average, wild caught sea basses (PFOS: 112-12,405 ng/kg, median 1345 ng/kg; PFOA: 9–487 ng/kg, median 28 ng/kg) showed higher levels than intensively farmed sea basses (PFOS: 11–105 ng/kg, median 32 ng/kg; PFOA: 9–51 ng/kg, median 21 ng/kg). Significant differences among the various rearing systems were also observed, with extensively-farmed subjects presenting relatively higher levels of both compounds compared to intensively farmed. Moreover, a certain variability among wild fish caught from different sampling sites was observed, confirming that PFASs contamination, which reached in some cases noticeable concentrations, might be influenced by the geographical origin. •Extensive single species investigation of PFASs presence in sea bass fillet.•Intensively farmed fishes are significantly less contaminated than wild-caught fishes.•Contamination is likely influenced by samples place of origin.